Studying rotational dynamics of epichlorohydrin using a Timepix3 camera - Chaleunrath-Pham, Lana (My University, 2025)
In the field of ultrafast atomic, molecular, and optical physics, our goal is to study the dynamics of molecules. This thesis focuses on the rotational dynamics of chiral molecules induced by a laser pulse. Molecular rotations are quite fast, thus femtosecond laser pulses are used to drive the rotation as well as to monitor this rotation. A pump pulse is used to bring the molecule into motion and a probe pulse is used to break the molecule into ionic fragments. The momenta of these fragments are studied to understand the orientation and rotational motion of the initial molecule. A significant portion of this thesis describes the implementation and synchronization of a Timepix3 camera into an existing experimental setup. Unlike a conventional camera which records the intensity of light onto pixels, the Timepix3 camera records the Time Of Arrival (TOA) of a light signal for each pixel and how long that signal stayed over a preset threshold (Time Over Threshold (TOT)). The pixels in the Timepix3 camera function independently from each other and collects the spatial coordinates, TOA, and TOT of an ion that lands on the detector. When used with a Velocity Map Imaging (VMI) spectrometer, the collected information can be used to find the mass over charge ratio and momenta of charged particles. After the implementation of the Timepix3 camera, we investigated the rotations of the chiral molecule epichlorohydrin. The pump pulse induces rotational motion of the molecule’s most polarizable axis, which causes the molecule to align and unalign itself with the polarization of the laser. The pump pulse also induces motion around the most polarizable axis. Simple symmetric molecules do not have a preference for the direction in which they rotate around this axis, but theory suggests that chiral molecules may have a preference. A portion of this thesis looks into how epichlorohydrin rotates and if it favors spinning in a particular direction, especially when comparing the left-handed and right-handed isomers.
Keywords: Rotational dynamics; Epichlorohydrin; Molecular dynamics; Timepix3 camera; Velocity map imaging